PENGARUH INTENSI, MOTIVASI, DAN PEMAHAMAN GURU TERHADAP IMPEMENTASI PENDIDIKAN INKLUSIF - MULYONO, RACHMAT; SUHYANTO, OTONG; SIRON, YUBAEDI; ROCHIMAH, NUR (Jurnal Pendidikan Usia Dini, 2017)
Abstract: The objective of the research was to find out the empirical information of the effect of intention, motivation, and teacher understanding on the implementation of inclusive education. The research used path analysis techniques. It conducted the elementary-school-teacher in East Jakarta, Indonesia. The simple random sampling technique is applied, which 50 teachers involved as the research sample. Empirical findings of the research revealed that: 1) There is no direct a positive effect of intention to the implementation of inclusive education; 2) There is no direct a positive effect of motivation to the implementation of inclusive education; 3) There is no direct a positive effect of teacher understanding to the implementation of inclusive education; 4) There is no direct positive effect of intention to the teacher understanding; 5) There is direct positive effectof motivation to the teacher understanding; 6) There is direct positive effect of intention to the motivation. Keywords: implementation of inclusive education, intention, motivation, teacher understanding, children with special needs. Abstrak: Tujuan penelitian ini untuk mencari informasi empiris tentang pengaruh intensi, motivasi, dan pemahaman guru terhadap implementasi pendidikan inklusif. Penelitian ini menggunakan analisis jalur. Penelitian ini mengukur perilaku guru SD di Jakarta Timur, Indonesia. Penelitian ini menggunakan teknik simple random sampling dengan melibatkan 50 guru. Temuan empiris mengungkapkan bahwa: 1) Tidak ada pengaruh langsung positif langsung intensi terhadap pendidikan inklusif; 2) Tidak ada pengaruh langsung positif motivasi terhadap pendidikan inklusif; 3) Tidak ada pengaruh langsung positif pemahaman guru terhadap pendidikan inklusif; 4) Tidak ada pengaruh positif langsung intensi terhadap pemahaman guru; 5) Ada pengaruh langsung motivasi terhadap pemahaman guru; 6) Ada pengaruh langsung intensi terhadap motivasi. Kata Kunci: implementasi-pendidikan-inklusif, intensi, motivasi, pemahaman guru, anak berkebutuhan-khusus